2018
DOI: 10.1093/jxb/ery253
|View full text |Cite
|
Sign up to set email alerts
|

TILLER ANGLE CONTROL 1 modulates plant architecture in response to photosynthetic signals

Abstract: Light serves as an important environmental cue in regulating plant architecture. Previous work had demonstrated that both photoreceptor-mediated signaling and photosynthesis play a role in determining the orientation of plant organs. TILLER ANGLE CONTROL 1 (TAC1) was recently shown to function in setting the orientation of lateral branches in diverse plant species, but the degree to which it plays a role in light-mediated phenotypes is unknown. Here, we demonstrated that TAC1 expression was light dependent, as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…We previously reported that overexpression of TAC1 in plum trees resulted in wider branch angles 17 . However, we also reported TAC1 overexpression only partially complemented the tac1 Arabidopsis mutant phenotype, and in 24-hour light or dark conditions TAC1 overexpression in Col had little effect on branch angle 3,18 . In contrast, 35 S::AtLAZY4/DRO1 in Arabidopsis exhibited more vertically oriented lateral shoots as a result of narrower branch angles, as well as upward curled leaves 6 .…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…We previously reported that overexpression of TAC1 in plum trees resulted in wider branch angles 17 . However, we also reported TAC1 overexpression only partially complemented the tac1 Arabidopsis mutant phenotype, and in 24-hour light or dark conditions TAC1 overexpression in Col had little effect on branch angle 3,18 . In contrast, 35 S::AtLAZY4/DRO1 in Arabidopsis exhibited more vertically oriented lateral shoots as a result of narrower branch angles, as well as upward curled leaves 6 .…”
Section: Resultsmentioning
confidence: 63%
“…Plant material, Genotyping, and Branch Angle Measurements. The Arabidopsis tac1, lazy1, prom-LAZY1::GUS, and 35 S::TAC1 plants were previously described 3,4,18 . The tac1;lazy1 homozygous double mutant lines were generated by crossing the single mutants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In poplar, the overexpression of the LAZY1 gene reduces branch angles, whereas the overexpression of tiller angle control 1 (TAC1) increased the branch angle and promoted an outward branch growth orientation 9 . Similarly, plants with reduced or no TAC1 expression exhibit more vertical shoot angles, as observed in Arabidopsis, maize, rice, and peach [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 76%
“…Dardick et al (2013) showed that region II of LAZY genes contains a GwL(A/T)GT motif, which places LAZY genes within a larger family, IGT, to which the Tiller Angle Control 1 (TAC1) gene belongs. Interestingly, TAC1 functionally opposes LAZY by increasing the tiller angle in rice (Yu et al, 2007) and branch angles in peach (Prunus persica) trees (Dardick et al, 2013) and Arabidopsis inflorescences (Waite and Dardick, 2018).…”
mentioning
confidence: 99%